Strategi Pelestarian Tradisi Katoba sebagai Media Pendidikan Islam pada Masyarakat Etnis Muna di Sulawesi Tenggara - Rukmina Gonibala; Ardianto Ardianto; Hadirman Hadirman (Journal of Islamic Education Policy, 2018)
ABSTRACT., The purpose of this study was to describe the preservation strategy of the katoba’s tradition as a medium of Islamic education in Muna ethnic communities at Southeast Sulawesi. Katoba was a life cycle tradition that deals with the practice of Islamic values which carried out hereditary by Muna ethnic communities. In Muna ethnic communities, the Katoba tradition was understood as a ritual of "repentance", or "child islamization" which aged 7-11 years old. In its implementation, the katoba tradition contains the values of Islamic education that are represented, both verbally and nonverbally. This study used a qualitative approach with the research location in Muna district and West Muna District, at Southeast Sulawesi Province. By using the interactive analysis, this study produced the facts about the preservation of the katoba tradition as a medium of Islamic education in the Muna community which carried out by (1) inheriting katoba values in the family environment, (2) preserving the Muna language, (2) increasing the professionalism of imamu, and (4) preservation through "Katoba-insightful" teaching and research.               Keywords: strategy of preservation, katoba tradition, Muna ethnic communities ABSTRAK., Tujuan penelitian ini adalah menggambarkan strategi pelestarian tradisi katoba sebagai media pendidikan Islam pada masyarakat etnis Muna di Sulawesi Tenggara. Katoba adalah tradisi siklus hidup yang bertalian dengan praktik nilai-nilai Islam yang dilaksanakan secara turun-temurun oleh masyarakat etnis Muna. Bagi masyarakat etnis Muna, tradisi katoba dipahami sebagai ritual “pertobatan”, atau “pengislaman anak” berusia 7-11 tahun. Dalam pelaksanaannya tradisi katoba mengandung nilai-nilai pendidikan Islam yang direpsentasikan, baik secara verbal maupun nonverbal. Penelitian ini menggunakan pendekatan kualitatif dengan lokasi penelitian di kabupaten Muna dan Kabupaten Muna Barat Propinsi Sulawesi Tenggara. Menggunakan analisis interaktif, penelitian ini menghasilkan fakta-fakta strategi pelestarian tradisi katoba sebagai media pendidikan Islam pada masyarakat Muna dilakukan dengan langkah-langkah (1) pewarisan nilai-nilai katoba di lingkungan keluarga, (2) pelestarian bahasa Muna, (2) peningkatan profesionalisme imamu, dan (4) pelestarian melalui pengajaran dan penelitian “Berwawasan Katoba”. Kata Kunci: strategi pelestarian, tradisi katoba, masyarakat etnis Muna